2014
DOI: 10.14445/22315381/ijett-v18p256
|View full text |Cite
|
Sign up to set email alerts
|

Study of Structural Strength and Behavior of Concrete Filled Double Skin Columns

Abstract: Column is a major Axial load transferring Member in most of the structures. According to the revised seismic codes columns should be have better flexural strength in addition to the Axial load carrying capacity. It is been a major concern in construction industry in previous few years to increase the column strength. Concrete-Filled Double Skin Tubes (CFDST) is one of the latest innovations in Structural engineeringThe CFDST members were first designed for vessels to resist extreme external pressure but due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The global stability of these CFDST members is considerably enhanced, due to the presence of inner steel tubes and hence increasing the section modulus of CFDST columns (Elchalakani et al, 2018;Uenaka et al, 2010;Wei et al, 1994). Under various loading conditions, in experimental and finite element investigations, it has been observed that efficient interaction of outer tube, concrete core and inner tube results in better confinement of concrete core, enhanced local and global stability, better ductility and good damping characteristics, compared to CFT columns (Elchalakani et al, 2002(Elchalakani et al, , 2019Han et al, 2007;Hassan and Sivakamasundari, 2014;Shakir-Khalil, 1991;Tao et al, 2003;Yan et al, 2021;Zhao and Grzebieta, 2002). It has also been observed that the performance of CFDST columns, is better than RCC columns (Hassan and Bhat, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The global stability of these CFDST members is considerably enhanced, due to the presence of inner steel tubes and hence increasing the section modulus of CFDST columns (Elchalakani et al, 2018;Uenaka et al, 2010;Wei et al, 1994). Under various loading conditions, in experimental and finite element investigations, it has been observed that efficient interaction of outer tube, concrete core and inner tube results in better confinement of concrete core, enhanced local and global stability, better ductility and good damping characteristics, compared to CFT columns (Elchalakani et al, 2002(Elchalakani et al, , 2019Han et al, 2007;Hassan and Sivakamasundari, 2014;Shakir-Khalil, 1991;Tao et al, 2003;Yan et al, 2021;Zhao and Grzebieta, 2002). It has also been observed that the performance of CFDST columns, is better than RCC columns (Hassan and Bhat, 2021).…”
Section: Introductionmentioning
confidence: 99%